Released Items for the Eighth Grade Mathematics [and] Science CSAP - Colorado State Dept. of Education, Denver; Colorado State Dept. of Education, Denver ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 2000)
This booklet contains released test items from the spring 2000 administration of the eighth grade mathematics and science tests of the Colorado Student Assessment Program. Items are released with the correct answers, and the scoring guide is included for selections from the constructed response portion of the science test. (SLD)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Achievement Tests; Grade 8.; Junior High Schools; Mathematics Tests; Science Tests; State Programs; Test Construction; Test Items; Testing Programs; Colorado Student Assessment Program; Colorado; Tests/Questionnaires.